Breaking down barriers: Overcoming silo mentality in bureaucratic reform - Guna, Tedo Hindami; Suparno; Kertati, Indra (Journal of Sustainability, Society, and Eco-Welfare, 2024)
Background: Silo mentality has emerged as a significant obstacle in the bureaucratic reform process in Indonesia. This paper aims to investigate the underlying causes, adverse effects, and potential solutions to address silo mentality within the context of bureaucratic reform in government organizations.The study employs a qualitative approach, conducting a comprehensive review of relevant literature and analyzing the phenomenon of silo mentality in government organizations. Methods: The research draws upon various scholarly articles, government reports, and case studies to gain insights into the dynamics of silo mentality and its impact on bureaucratic reform efforts. Findings: The findings reveal that silo mentality stems from a range of factors, including leadership issues, lack of effective communication channels, and a focus on individual goals rather than organizational objectives. The presence of hierarchical structures and a lack of transparency in information sharing across different divisions contribute to the formation of silos. The impacts of silo mentality are far-reaching, resulting in reduced productivity, decreased employee morale, and diminished customer satisfaction. Conclusion: To overcome these challenges, the paper proposes several strategies. These include ensuring employee vision convergence, achieving common goals collectively, providing motivation and incentives, precise execution, and fostering collaboration among departments. The bureaucratic reform in Indonesia aims to establish a competent, professional, and integrity-driven bureaucracy that is free from corruption and serves the public effectively. However, the presence of a silo mentality hinders the realization of these goals by creating barriers to communication, collaboration, and innovation. Future research should focus on developing practical frameworks and tools to facilitate the implementation of the proposed strategies for breaking down silos and promoting a collaborative work environment within government organizations undergoing bureaucratic reform. Empirical studies examining the effectiveness of these strategies in real-world settings would provide valuable insights into their applicability and potential for success. Additionally, exploring the role of technology in enabling seamless communication and collaboration across departments could offer new avenues for addressing silo mentality in the digital age. Novelty/Originality of this Study: The novelty of the 'silo mentality' phenomenon within the context of bureaucratic reform in Indonesia, identifying its causes, impacts, and proposing strategies to overcome it in order to achieve effective governance.